KARAKTER WANITA DALAM TRADISI JAWA - Sarno Hanipudin; Yusri Amalia Habibah (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
: This paper tries to present a gender discourse which is still interesting to study, which is related to character. Lots of character terminology, especially those related to the feminist side, will be more interesting because for some genders they have a 'patent' side of character that cannot be changed. Character is a characteristic of objects or individuals, these characteristics are original and rooted in the personality of the object or individual and are a machine that drives how a person acts, behaves and responds to something. Character is also something that distinguishes objects or individuals from one another. Meanwhile, the character of Javanese women is the character possessed by Javanese women, namely Nrimo ing pandum, naive, obedient, caring for feelings, hardworking, generous, diligent, caring for others.Keywords: Character, Woman, Javanese Tradition